2017
DOI: 10.1007/s00701-017-3391-x
|View full text |Cite
|
Sign up to set email alerts
|

Right Brodmann area 18 predicts tremor arrest after Vim radiosurgery: a voxel-based morphometry study

Abstract: Routine baseline structural neuroimaging predicts TSTH improvement 1 year after Vim RS. The relevant anatomical area is the right visual association cortex (BA 18, V2). The question whether visual areas should be included in the targeting remains open.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
(43 reference statements)
5
17
0
Order By: Relevance
“…Moreover, using the same methodology (i.e., seed-based approach) and in a second study, we coined the term cerebello-thalamo-visuo-motor network to describe the fact that pretherapeutic VLV FC with right visual association area (Brodmann area, BA19) predicted 1-year activities of daily living (ADL; Bain et al, 1993) decrease. This revelation of visual areas implicated in ET followed other publications from our group, on the same topic, on both functional (please see below) and structural aspects Tuleasca, Witjas, van de Ville, et al, 2017).…”
Section: Dear Editorsupporting
confidence: 79%
“…Moreover, using the same methodology (i.e., seed-based approach) and in a second study, we coined the term cerebello-thalamo-visuo-motor network to describe the fact that pretherapeutic VLV FC with right visual association area (Brodmann area, BA19) predicted 1-year activities of daily living (ADL; Bain et al, 1993) decrease. This revelation of visual areas implicated in ET followed other publications from our group, on the same topic, on both functional (please see below) and structural aspects Tuleasca, Witjas, van de Ville, et al, 2017).…”
Section: Dear Editorsupporting
confidence: 79%
“…The importance of brain visual areas in tremor pathogenesis has been recently investigated by using a visual task of increasing difficulty to illustrate the impact of visuospatial network in tremor augmentation (Archer et al, 2018). Furthermore, recent series of investigations suggested that structural and functional changes of the visual cortex could be a preoperative predictor of optimum tremor outcome after ablative radiosurgery (Tuleasca et al, 2017(Tuleasca et al, , 2018b(Tuleasca et al, , 2018c.…”
Section: The Tremor Network and Pattern Of Beneficial Dbs Connectivitymentioning
confidence: 99%
“…Neuroimaging, including multimodal MRI and PET, could provide additional insights into ET physiopathology. In this vein, recent MRI studies have reported the involvement of the visuo-motor network in ET in VBM studies 12,13 and fMRI studies 14,15 .…”
Section: Introductionmentioning
confidence: 99%